2019
DOI: 10.5312/wjo.v10.i8.299
|View full text |Cite
|
Sign up to set email alerts
|

Rigid locked nail fixation for pediatric tibia fractures - Where are the data?

Abstract: Tibial shaft fractures are common injuries among the pediatric and adolescent population. Conservative treatment remains the preferred treatment. However, over the last two decades, there has been an increasing trend of operative fixation in pediatric tibia fractures, commonly with intramedullary nail fixation (IMN). Elastic stable intramedullary nails (ESIN) are heavily used especially in skeletally immature patients as they are physeal respecting and the technique for insertion is familiar. Alternatively, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Very little is written about rigid intramedullary nailing (RIMN) in adolescents, given the transphyseal nature of a traditional tibial nail starting point. This obviates the need for consideration of other techniques given the potential for subsequent physeal arrest with the transphyseal technique [ 19 ]. One group studied the use of RIMN in adolescents and did not show an increased incidence of growth arrest, but their technique was not physeal-sparing [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very little is written about rigid intramedullary nailing (RIMN) in adolescents, given the transphyseal nature of a traditional tibial nail starting point. This obviates the need for consideration of other techniques given the potential for subsequent physeal arrest with the transphyseal technique [ 19 ]. One group studied the use of RIMN in adolescents and did not show an increased incidence of growth arrest, but their technique was not physeal-sparing [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This technique could be used and alleviate the difficult decision in determining the borderline "too young" adolescent patient with open physis to receive a reamed intramedullary nail, where the risk of physis arrest still is uncertain. 19 The technique would allow for relative stability with a load-sharing construct and minimally invasive aspects of EIN while decreasing the morbidity associated with open plating. 1 Recent studies have shown that elective hardware removal risks may not outweigh the benefit but is required in pediatric patients for continued growth.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric long bone fractures do not require reamed locked intramedullary fixation, such as what is required in the adult population. This technique could be used and alleviate the difficult decision in determining the borderline “too young” adolescent patient with open physis to receive a reamed intramedullary nail, where the risk of physis arrest still is uncertain 19. The technique would allow for relative stability with a load-sharing construct and minimally invasive aspects of EIN while decreasing the morbidity associated with open plating 1.…”
Section: Discussionmentioning
confidence: 99%